Knowledge of Breast Feeding Positioning among Primigravida Mothers - Ragheesa Farooq, Mehwish Khalid, Saba Murtaza, Mubashra Aziz, Anum Khalid, Zainab Hassan, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Breastfeeding is the natural procedure of feeding a baby with mother’s milk which is important for healthy life of a baby Most common breastfeeding positions for nursing a newborn are cross cradle hold, cradle hold, side-lying and football hold Study design: Descriptive cross-sectional study. Methodology: Non- probability convenient sampling technique were used for this study. The number of primigravida women participated in this study was 350. Instrument used for the study was the standardized questionnaire which gathered details on socio-demographic factors and maternal traits of primigravida women such as their knowledge about postures, positioning, hold practice and latch-on practice. Data was evaluated by using SPSS v.23. Qualitative data was presented as percentage and frequency. Results: Almost, 56.6% participants had good knowledge while and 43.3% had a poor knowledge of breastfeeding positioning. 68.6% practiced advisable breastfeeding posture. Cross cradle hold (56.9%) was the most common breastfeeding technique with 18.6% cradle hold, 17.7% football hold and 6.9% side-lying position. About 75.7% mothers had baby to breast latch-on practice. Practical Implication: This study brought attention towards the assessment of knowledge regarding different breastfeeding positions. Moreover, this study helped physiotherapists to evaluate the musculoskeletal problems in early stage so that they can provide awareness to mothers related effective breastfeeding positioning. Conclusion: It was concluded that primigravida mothers showed the good knowledge of breastfeeding positioning. As all the mothers practiced advisable breastfeeding postures, adopted sitting on the side of bed to breastfeed, worked on cross-cradle hold and baby-to breast latch-on. Keywords: Breastfeeding Positioning, Knowledge and Primigravida mothers